A dual-energy-demand-indices-based evaluation procedure of damage-control frame structures with energy dissipation fuses. Issue 95 (April 2017) - Ke, Ke; Yam, Michael C.H.; Ke, Shuizhou
Abstract: The primary objective of this research is to extend energy balance concept in seismic behavior evaluation of low-to-medium rise frame systems with energy dissipation fuses dominated by racking deformations. At its core, energy demand indices under ground motions considering both peak responses and cumulative responses are quantified to develop a dual-energy-demand-indices-based procedure for damage-control behavior evaluation. Firstly, based on the experimentally validated hysteretic feature and representative ground motion ensembles, a parametric study is conducted considering the demand indices of the energy factor and the cumulative ductility. Results of the indices distribution and dispersion are presented in detail. Subsequently, a stepwise procedure that accounts for the peak demand and the cumulative demand is constructed. Then, the procedure is applied in prototype structures for validation. Results indicate that the consideration of dual energy demand indices is necessary for evaluation of systems with fuses, and these indices are influenced by structural nonlinear parameters and ground motions properties. The procedure based on the dual energy demand indices can be used to evaluate the structural damage-control behavior with satisfactory accuracy considering the peak response, the cumulative response, and the energy distribution along stories. Highlights: Seismic demand of systems with fuses is quantified by dual energy demand indices. The effect of nonlinear parameters on the demand indices are clarified by a parametric study. The necessity of considering these demand indices is validated. A dual-energy-demand-indices-based procedure is proposed. The application of the proposed procedure is illustrated in detail.